2001
DOI: 10.1002/1097-0215(20010601)92:5<767::aid-ijc1247>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Types of dietary fat and breast cancer: A pooled analysis of cohort studies

Abstract: Recently, there has been interest in whether intakes of specific types of fat are associated with breast cancer risk independently of other types of fat, but results have been inconsistent. We identified 8 prospective studies that met predefined criteria and analyzed their primary data using a standardized approach. Holding total energy intake constant, we calculated relative risks for increments of 5% of energy for each type of fat compared with an equivalent amount of energy from carbohydrates or from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
235
1
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(259 citation statements)
references
References 34 publications
14
235
1
9
Order By: Relevance
“…The protective effect of MUFA in older women support is consistent with the Swedish mammography cohort on postmenopausal women (Wolk et al, 1998) but not with a nested casecontrol (Wirfalt et al, 2002) and several cohort studies, which, with some exceptions (Holmes et al, 1999;Voorrips et al, 2002), have reported no or even a positive association with MUFA (Velie et al, 2000;Smith-Warner et al, 2001;Boyd et al, 2003;Cho et al, 2003;Kim et al, 2006;Thiebaut et al, 2007). We also found a protective effect of PUFA in older women, as in a few case -control studies (Boyd et al, 2003) but not with any earlier prospective cohorts (Boyd et al, 2003;Kim et al, 2006;Thiebaut et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…The protective effect of MUFA in older women support is consistent with the Swedish mammography cohort on postmenopausal women (Wolk et al, 1998) but not with a nested casecontrol (Wirfalt et al, 2002) and several cohort studies, which, with some exceptions (Holmes et al, 1999;Voorrips et al, 2002), have reported no or even a positive association with MUFA (Velie et al, 2000;Smith-Warner et al, 2001;Boyd et al, 2003;Cho et al, 2003;Kim et al, 2006;Thiebaut et al, 2007). We also found a protective effect of PUFA in older women, as in a few case -control studies (Boyd et al, 2003) but not with any earlier prospective cohorts (Boyd et al, 2003;Kim et al, 2006;Thiebaut et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…One study found that risks were increased when chicken was consumed with skin suggesting that fat rather than muscle meat may be the cause (Ronco et al, 2003). Other studies have suggested a link between fat and breast cancer (Howe et al, 1991;Willett et al, 1992;Hunter et al, 1996;Smith-Warner et al, 2001;Boyd et al, 2003;Cho et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption has been associated with increased risk of various types of cancer [49]. For instance, risk of breast cancer is increased by moderate consumption of alcohol [50,51], but not further increased by heavy drinking (i.e., at least 60 g/day of alcohol) [51]. A possible biological mechanism for this association could be that moderate alcohol consumption increases IGF-I production by the liver, which is not further increased in heavy drinkers due to alcohol-induced liver damage [25].…”
Section: Discussionmentioning
confidence: 99%